Are good knowledge and positive attitudes regarding the cigarettes and other tobacco products act prevalent among rural Indian adults? - R., Pracheth; N., Varun; Y. M., Ravindra; S., Preethi; K., Tasmiya; N. I., Naveed (International Journal Of Community Medicine And Public Health, 2017)
Background: Cigarettes and other tobacco products (COTPA) Act is a legislation passed to curb tobacco use in India by imposing restrictions on tobacco products. This study appraised knowledge and attitudes regarding COTPA Act among adults in a rural area and elicited socio-demographic predictors of knowledge and attitudes regarding COTPA Act among study participants. Methods: A cross-sectional study was conducted from September to December 2014 on adults (aged ≥18 years) in a rural area of Coastal Karnataka. A pre-designed, pre-tested proforma was used to collect information from study participants regarding their knowledge and attitudes about COTPA Act. Knowledge and attitude scores were computed. A score of ≥4 was good knowledge and ≥3 was regarded as positive attitudes. Results: Nearly 49.14% had good knowledge, while 51.29% displayed positive attitudes. Those belonging to upper and upper middle socio-economic class (Class I+Class II) had higher odds for good knowledge (AOR=2.09, 95% CI=0.82-5.92), when compared to their counterparts belonging to other socio-economic classes. Age ≥60 years (AOR=3.80, 95% CI= 0.30-9.98), education beyond primary school (AOR=2.88, 95% CI=1.24-6.19), upper and upper middle class socio-economic status (AOR=3.68, 95% CI=1.34-7.02) were the key predictor variables for positive attitudes. Conclusions:Nearly half the study participants had good knowledge and positive attitudes towards COTPA Act. High socio-economic status could predict good knowledge, while age ≥60 years, education beyond primary school and a high socio-economic status were the key variables predicting positive attitudes. Educational campaigns can help improve knowledge. Assessment of knowledge and attitude is imperative prior to implementation of policies to ensure effectiveness.